Progress of seabass, Lates calcarifer (Bloch, 1970) culture in Bangladesh: Field-level updates from the Bhola and Satkhira Districts (International Journal of Agricultural Research, Innovation and Technology, 2023)
Since the high market value of seabass, Lates calcarifer (Bloch, 1970), mainly found in Bangladesh's coastal waters and tidal rivers of Bangladesh, farmers in those areas cultivate it alongside carp fish in ponds and shrimp farms. Even though farming began many years ago, progress in overcoming obstacles of only natural sources for hatchlings, supplemental feeding, and knowledge on advanced farming management in seabass farming at the field level has been prolonged. This study discusses the current farming and trading of seabass in Bangladesh's coastal districts. Seabass fry is collected from rivers and estuarine areas, grown in hatcheries or ponds, and sold to farmers in large sizes. Some farmers cultivate this fry in mixed fish culture ponds in the extensive method; some farmers cultivate them with carp fish in a semi-intensive method. Seabass feeds only live feed (Tilapia and carp fishes fry); continuous supply is difficult and expensive. In these ponds, seabass is cultivated in the traditional method in 18–20 months, weighing 7-8 kg, and in the advanced traditional method in 1 year, weighing 2-3 kg. The profit percentage of seabass farming with the semi-intensive method is 77.42%. To expand this profitable fish farming, it is crucial to acclimate the fish to induced breeding and supplemental food. The institutions involved should not work in isolation but rather collaborate on developing induced breeding techniques and expanding seabass farming. In this case, prosperous seabass farming countries' experience can be applied.Int. J. Agril. Res. Innov. Tech. 12(2): 117-125, December 2022